2017
DOI: 10.1177/1010539516684533
|View full text |Cite
|
Sign up to set email alerts
|

Fukushima Mothers’ Concerns and Associated Factors After the Fukushima Nuclear Power Plant Disaster

Abstract: This study aimed to clarify the frequency of and temporal changes in the content of mothers' free written opinions obtained in the Fukushima Health Management Survey Pregnancy and Birth Survey from 2011 to 2013. A self-administered questionnaire was mailed to women who delivered babies in Fukushima Prefecture. The questionnaire asked about maternal and child health. Expression of mothers' concerns about radiation decreased over time. Common to the top 5 codes across the 3 years were "radiation effect on fetus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
0
19
1
Order By: Relevance
“…Seven articles (29%) examined governing factors and explained the variance of risk perception [ 7 , 16 , 17 , 18 , 19 , 20 , 32 ], 10 (42%) examined the effects of risk perception or anxiety [ 7 , 11 , 12 , 21 , 22 , 23 , 24 , 25 , 33 , 34 ], and five (21%) [ 18 , 20 , 29 , 30 , 31 ] reported modifiability due to interventions (three of which also explain variance of risk perception factors). Three articles and the two surveys (20%) assessed risk perception and anxiety only [ 26 , 27 , 28 , 35 , 36 ], and did not examine governing factors and effects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven articles (29%) examined governing factors and explained the variance of risk perception [ 7 , 16 , 17 , 18 , 19 , 20 , 32 ], 10 (42%) examined the effects of risk perception or anxiety [ 7 , 11 , 12 , 21 , 22 , 23 , 24 , 25 , 33 , 34 ], and five (21%) [ 18 , 20 , 29 , 30 , 31 ] reported modifiability due to interventions (three of which also explain variance of risk perception factors). Three articles and the two surveys (20%) assessed risk perception and anxiety only [ 26 , 27 , 28 , 35 , 36 ], and did not examine governing factors and effects.…”
Section: Resultsmentioning
confidence: 99%
“…Although no surveys or studies statistically tested changes in risk perception or anxiety over time, two articles reported descriptive data. Ito et al [ 28 ] reported the frequency of and changes over time in the content of mothers’ opinions obtained in the FHMS Pregnancy and Birth Survey from 2011 to 2013. Mothers’ concerns about radiation decreased over time (rate of opinion about radiation effect on fetus: 29.8% in 2011, 26.8% in 2012, 17.4% in 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17) In particular, after the incident, parental requests for internal contamination examinations of their children and parental anxiety concerning their children's health were high. 18) There was an increase in internal contamination examinations of children in addition to high levels of Fukushima food evasion by the parents/guardians of children. 19) The concern for radiation exposure was manifested in a desire for regular assessment of internal contamination levels among the parents/ guardians of children.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mothers felt anxious about the effects of radiation on their children's health and their future (Ito et al, ; Yoshii et al, ). The Fukushima health management survey demonstrated that women were more concerned about immediate and delayed health effects than men (Suzuki et al, ).…”
Section: Introductionmentioning
confidence: 99%